Leaning in to "Muddy" Interviews. (February 2014) - Lippke, Lena; Tanggaard, Lene
Over the last few decades, qualitative research has been acknowledged as a peopled practice in which subjectivities come into play. The main argument presented in this article is that qualitative research involves "muddy, " troublesome, interactional passages, because of a complex interplay between subjectivities, situated identities, emotions, and conversational genres. Based on ethnographic fieldwork at a Danish Vocational Educational Training College, we introduce the concept of "leaning in" to provide an analytical grasp of the "muddy" interactional tension field in an interview situation, in which situated identities among the participants cross each other. We emphasize the value of daring to lean in to the muddiness of peopled research, use it as an analytical tool and present it in its imperfect form. This approach contributes to transparency in qualitative research, opens up the data in a new way and generates insights and results that would not otherwise emerge.